Technoference: Technology as 'Third Person' in Romantic and Family Relationships - Shofwatun Amaliyah; Menik Agustina (Universitas Pendidikan Ganesha, 2023)
In the digital age, using technology has become a necessity for humans. Technology not only facilitates interaction, it can also be a distraction in relationship termed “technoreference”. This paper aims to provide a descriptive explanation of the negative impact of technology use on interpersonal relationships. Topics concerning the issue of technoference in interpersonal relationships include: (1) the concept of technoference in smartphone use; (2) technoference in romantic relationships; (3) technoference in family relations. According to the findings of several relevant scientific studies and researches, technoference is a disruption that occurs in everyday interactions as a consequence of the usage of technological devices. Technoference in romantic relationships indicates poor relationship quality and relationship dissatisfaction. Meanwhile, technoference in family relationships contributes to suboptimal parent-child interactions and child problem behaviors.